Acumuladores de animais : caracterização do perfil psicopatológico - Ferreira, Elisa Arrienti (2017)
Introduction: The Animal Hoarding Disorder is a complex psychopathology that produces significant impacts on the lives of individuals. Objects: The present study resulted in to two studies, each with its own proposal. Study 1 aimed to characterize the sociodemographic profile of animal hoarders of a city in the south of Brazil, and to propose that the Animal Hoarding Disorder becomes a new nosological category. Study 2 sought to describe the psychopathological comorbid symptoms to the animal hoarding disorder and to verify the association between the variables age, sex, marital status, income, number of animals, time accumulating animals and the expression of psychopathological symptoms. Method: The final sample of the both studies consisted of 33 individuals. The mean age of the sample was 61.39 years (SD = 12.69), and the mean educational level was 9.39 years (SD = 4.40). The mean number of self-reported animals per household was 41.12 (± 24.41), in a total of 1357 animals, 915 (68%) dogs, 382 (28%) cats and 50 (4%) ducks. To collect data from study 1, a socio-demographic data sheet, a semi-structured interview, and a veterinarians' report on the state of animal health and sanitation were used. In study 2, a sociodemographic data sheet and a semi-structured clinical interview, based on the DSM-5 Level 1 Symptom Transversal Scale. The data were organized in a bank, created in the program Statistical Package for the Social Sciences. Statistical analyzes, descriptions and associations were performed through the Chi-square. Results: Study 1 found a higher prevalence of women (73%) and elderly (64%) in the sample, corroborating the literature findings. Significant differences were observed between the accumulation disorder and the animal accumulation disorder. It has been found that, contrary to what happens in the accumulation of objects, the accumulated animals do not usually obstruct the spaces of the houses. The process of discarding or donating animals is also different, since there is an affective bond with lives and not with inanimate objects. The results of study 2 showed as symptoms of depression (36%), mania (21%), obsessive-compulsive disorder (18%), anxiety (36%) and memory impairment (27%). Association analyzes revealed a higher occurrence of mania, panic, obsessive-compulsive, and memory impairment among participants who had hoarded animals for more than 20 years. Conclusion: In study 1, specific diagnostic criteria for Animal Hoarding Disorder were created, proposing that it become a new diagnostic category. It is believed that this proposition may arouse greater interest, both in clinical professionals and researchers, as well as encouraging new interventional research for this problem. In study 2, it was concluded that the animal hoarding presents, as comorbid, depressive symptoms, manic, obsessive-compulsive, anxiety and memory impairment. New research on the subject is suggested to help in the construction of specific protocols of this population, in order to minimize the suffering of individuals and animals.